The Ageing of Materials and Structures Towards Scientific Solutions for the Ageing of Our Assets - van Breugel, Klaas; Koleva, Dessi; Beek, Ton van (Springer International Publishing : Imprint: Springer, 2018)
This work is an overview of the state of art on Ageing of Materials and structures in the world. Ageing of materials is a natural phenomenon. Each material we use will age. This ageing will influence the performance of the object where the materials is used. Furthermore, the ageing will be affected by the surroundings in which the object is placed. The main focus of the book is on materials used in infrastructure, energy, buildings and industry. The book in effect establishes the definition of ageing and its main research topics that are relevant for society.